The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/molecules23020451
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Helps to Lessen Extinction Memory in Rats

Abstract: Memory extinction is referred to as a learning process in which a conditioned response (CR) progressively reduces over time as an animal learns to uncouple a response from a stimulus. Extinction occurs when the rat is placed into a context without shock after training. Docosahexaenoic acid (DHA, C22:6, n-3) is implicated in memory formation in mammalian brains. In a two-way active shuttle-avoidance apparatus, we examined whether DHA affects the extinction memory and the expression of brain cognition-related pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…In support of this, it has been previously reported that deficiencies in n-3 LCPUFA such as DHA in the brain, correlates with a reduction in the GluN2B amount leading to LTP impairment [93]. Moreover, the hippocampus of rats under treatment with DHA increases the expression of the NMDAR subunit GluN2B as well as in DHA-enriched cultured mouse hippocampal neurons [94,95].…”
Section: Discussionsupporting
confidence: 52%
“…In support of this, it has been previously reported that deficiencies in n-3 LCPUFA such as DHA in the brain, correlates with a reduction in the GluN2B amount leading to LTP impairment [93]. Moreover, the hippocampus of rats under treatment with DHA increases the expression of the NMDAR subunit GluN2B as well as in DHA-enriched cultured mouse hippocampal neurons [94,95].…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, DHA enhances spatial memory ability, stimulates neurogenesis, and protects the elderly from aging-related cognitive decline . In addition, a DHA treatment in rats resulted in changes in extinction memory and levels of brain cognition-related proteins . These findings demonstrate that there is a strong link between DHA and cognitive health.…”
Section: Introductionmentioning
confidence: 71%
“…15 In addition, a DHA treatment in rats resulted in changes in extinction memory and levels of brain cognition-related proteins. 16 These findings demonstrate that there is a strong link between DHA and cognitive health.…”
Section: Introductionmentioning
confidence: 77%
“…Confirming our finding that the GRP removal prolongs fear extinction in the Grp -/- mice, the GRP decreases fear memory reconsolidation when applied intraperitoneally immediately following recall in rats (Murkar, Kent, Cayer, James, & Merali, 2018). Also, GRP protein levels and Grpr mRNA levels are increased following treatment with drug docosahexaenoic acid, which leads to facilitation of fear extinction (Hashimoto, Hossain, Katakura, Mamun, & Shido, 2018). These findings support earlier observations that a removal of the GRP signaling in vivo leads to enhanced and prolonged fear memory and deficient fear extinction in Grpr -/Y mice (Chaperon et al, 2012; Martel et al, 2012; Shumyatsky et al, 2002).…”
Section: Discussionmentioning
confidence: 99%